Variable Step Size LMS Adaptive Filtering Based on Genetic Algorithm - Zhang, Hua Dong; Wu, Guo Hui; Shi, Jian (Applied Mechanics and Materials, 2013)
A common form of variable step size LMS algorithm is presented，which is derived by the extensive analysis about several variable step size LMS algorithm. Using genetic algorithm parameter optimization, the algorithm get the optimal valueα、β、m and h quickly and efficiently，and not rely on experience or method of trial and error. MATLAB simulation results confirmed the theoretical analysis, the algorithm took on good convergence and tracking properties，and could be widely used in modern digital communication systems.